Monitoring of the Gasoline Oxygenate MTBE and BTEX Compounds in Groundwater in Catalonia (Northeast Spain) - J. Fraile; J.M. Niaerola; L. Olivella; M. Figueras; A. Ginebreda; M. Vilanova; D. Barcela (The Scientific World Journal)
Headspace (HS) gas chromatography with flame ionisation detection (HS-GC-FID) and purge and trap (P) gas chromatography-mass spectrometry (P) were used for the determination of methyl-tert-butyl ether (MTBE) and benzene, toluene, and xylenes (BTEX) in groundwater. In this work, we present the first data on the levels of MTBE and BTEX in different groundwater wells in the area of Catalonia (northeast Spain). This monitoring campaign corresponded to 28 groundwater wells that were located near petrol service stations, oil refinery storage tanks, and/or chemical industry at different locations of Catalonia during the period of 1998/1999. The levels of MTBE detected varied between 4—300 μg/l, but two sites had MTBE levels up to 3 and 13 mg/l. In many cases, the BTEX levels were below 1 μg/l, whereas 7 sites had levels varying from 19 μg/l up to 3 mg/l. Most of them were related to leakage from underground tanks in petrol service stations, while the remaining three corresponded respectively to chemical industrial pollution of undetermined origin and to a leak from high-ground petrol tanks in petrochemical refinery factories. The aquifers involved were constituted by detritus coarse materials, sands, and conglomerates. Piezometric levels were roughly comprised between 3 and 40 m, and permeability (K) and transmissivity (T) values were estimated from field measurements.